Residual concentrations of the flukicidal compound triclabendazole in dairy cows' milk and cheese. - Imperiale, F. (2011)
Triclabendazole (TCBZ) is a flukicidal halogenated benzimidazole compound extensively used in veterinary medicine. Liver fluke control in lactating dairy cattle is difficult because treatment should be implemented only during the dry period to avoid milk residues. However, control in endemic areas is usually implemented as regular treatments three to four times a year, even during the lactating period. Thus, information on TCBZ milk excretion and the risk of the presence of drug residues in fluid milk and milk-derivate products is essential. The experimental aims were to evaluate the comparative disposition kinetics of TCBZ and its sulpho-metabolites in plasma and milk in lactating dairy cattle after the oral administration (12 mg kg(-1)) of TCBZ and to assess the pattern of residues in cheese made with milk from treated dairy cows. Both TCBZ sulphoxide and sulphone metabolites but not TCBZ were detected in milk (up to 36 and 144 h, respectively) and plasma (up to 144 h) after oral administration of TCBZ. Residual concentrations of TCBZ sulpho-metabolites were found in cheese made with milk from treated animals. The total average residual concentration in fresh cheese was 13.0-fold higher than that obtained in milk used for its elaboration. The high concentrations of TCBZ sulpho-metabolites recovered in fresh cheese should be seriously considered before milk from treated cows is used for making dairy products.